The art of watching films - Boggs, Joseph M. (Mayfield Pub. Co., 1996)
This introduction to film appreciation uses contemporary and popular American movies to help students develop critical skills in the analysis and evaluation of film. By suggesting what to look for and how to look for it, this text challenges students to sharpen their powers of observation, establish habits of perceptive watching, and discover complex aspects of film art that will further enhance their enjoyment of watching films.